Do Pharyngeal Surgeries for Treatment of Snoring and Sleep Apnea Have an Impact on Nasalance?. (23rd August 2013) - Karakoc, Omer; Akcam, Murat T.; Genc, Hakan; Birkent, Hakan; Binar, Murat; Gerek, Mustafa
Abstract : Objectives: Most of the surgeries used in the treatment of snoring and obstructive sleep apnea mainly target velopharyngeal structures, which play an important role in voice characteristics such as nasalance. The aim of this study is to assess the effect of different types of such surgical procedures including expansion sphincter pharyngoplasty, lateral pharyngoplasty, and anterior pharyngoplasty on nasalance. Methods: Forty‐four consecutive patients with primary snoring or obstructive sleep apnea (OSA) who underwent anterior palatoplasty, lateral pharyngoplasty, and expansion sphincter pharyngoplasty procedures were included in this study. All patients underwent a fully attended overnight polysomnography and detailed otolaryngologic examination. Nasalance studies were performed by using Nasometer II instrument (model 6400; Kay Elemetrics) preoperatively and 3 months after surgery. Results: The mean preoperative nasalance score for AP, LP, and SP groups were 49.06±10.72, 46.65±8.70, and 48±10.95, respectively. The mean postoperative nasalance score for AP, LP, and SP groups were 48.25±8.78, 46.82±5.2, and 49.36±10.81, respectively. There was no statistically significant difference in either group between preoperative and postoperative assessments of nasalance scores for all three passages. Seven patients experienced nasal regurgitation symptoms for fluids for a short time after LP, two patients after AP, and five patients after SP. None of these symptoms showed persistence, and they revealed at approximately 1‐month follow‐up. Conclusions: The results of this study showed that these surgical techniques did not lead to an objective velopharyngeal insufficiency, since no significant change in nasalance scores was observed.